A convenient multiplex PCR system for the detection of dystrophin gene deletions: a comparative analysis with cDNA hybridisation shows mistypings by both methods. Issue 5 (May 1991) - Abbs, S; Yau, S C; Clark, S; Mathew, C G; Bobrow, M
Abstract : Existing reactions for the multiplex PCR amplification of exons in the dystrophin gene have been modified to produce two multiplex reactions which separately cover the 5' and 3' major deletion 'hotspots' in the gene, and together detect approximately 98% of all deletions detectable by Southern cDNA hybridisation. A comparative study of 148 patients showed mistypings in both the cDNA hybridisation data (4%) and the PCR analysis (1.2%). We suggest means of circumventing the underlying problems in order to avoid mistyping and subsequent misdiagnosis, and conclude that, with appropriate precautions, multiplex PCR amplification can be the method of choice for detecting deletions in the dystrophin gene.